Handling data - Easingwood, Nick; Williams, John (ICT and Primary Mathematics, 2004)
We also described in detail the structure and usage of spreadsheets: how they can not only list and display data, but how they can mathematically utilise this information to produce further information such as totals, averages and measurements. As with a database, this information can be displayed in various forms.